How does tillage intensity affect soil organic carbon? A systematic review protocol. Issue 1 (December 2016) - Haddaway, Neal; Hedlund, Katarina; Jackson, Louise; Kätterer, Thomas; Lugato, Emanuele; Thomsen, Ingrid; Jørgensen, Helene; Isberg, Per-Erik
Abstract Background Soils contain the greatest terrestrial carbon (C) pool on the planet. Since approximately 12 % of soil C is held in cultivated soils, management of these agricultural areas has a huge potential to affect global carbon cycling; acting sometimes as a sink but also as a source. Tillage is one of the most important agricultural practices for soil management and has been traditionally undertaken to mechanically prepare soils for seeding and minimize effects of weeds. It has been associated with many negative impacts on soil quality, most notably a reduction in soil organic carbon (SOC), although still a matter of considerable debate, depending on factors such as depth of measurement, soil type, and tillage method. No tillage or reduced intensity tillage are frequently proposed mitigation measures for preservation of SOC and improvement of soil quality, for example for reducing erosion. Whilst several reviews have demonstrated benefits to C conservation of no till agriculture over intensive tillage, the general picture for reduced tillage intensity is unclear. This systematic review proposes to synthesise an extensive body of evidence, previously identified through a systematic map. Methods This systematic review is based on studies concerning tillage collated in a recently completed systematic map on the impact of agricultural management on SOC restricted to the warm temperate climate zone (i.e. boreo-temperate). These 311 studies were identified and selected systematically according to CEE guidelines. An update of the original search will be undertaken to identify newly published academic and grey literature in the time since the original search was performed in September 2013. Studies will be critically appraised for their internal and external validity, followed by full data extraction (meta-data describing study settings and quantitative study results). Where possible, studies will be included in meta-analyses examining the effect of tillage reduction ('moderate' (i.e. shallow) and no tillage relative to 'intensive' tillage methods such as mouldboard ploughing, where soil is turned over throughout the soil profile). The implications of the findings will be discussed in terms of policy, practice and research along with a discussion of the nature of the evidence base.